Expression dynamics of ISGs and chemokines in maternal whole blood as an indicator of healthy embryonic implantation in buffalo - KUMARI, RAJNI; DAYAL, SHANKER; RAMAN, ROHAN KUMAR; CHANDRAN, P C; KUMAR, SANJAY; RAY, PRADEEP KUMAR; KAMAL, REENA; KUMAR, JYOTI; DEY, AMITAVA; SARMA, KAMAL; KUMAR, UJJWAL (The Indian Journal of Animal Sciences, 2022)
Successful pregnancy establishment has a major influence on reproductive efficiencies of dairy buffaloes. This success depends on coordinated communications between conceptus and maternally derived cells, and any disturbance in this communication network during this process leads to early embryonic losses. Since, early embryonic losses is one of the prime cause of pregnancy failure in dairy buffaloes, present investigation was aimed to understand the expression dynamics and correlation pattern of Interferon tau stimulated genes and chemokines during peri-implantation period in dairy buffaloes through transcriptional profiling followed by Principal Component Analysis. Our study revealed upregulation of all the candidate genes in maternal whole blood across the parity, emphasizing the involvement of immune responses as signatures for healthy pregnancy. Understanding these embryo-maternal communication signals offers potential to prevent incidences of early embryonic losses and can provide insights on possible targets for therapy too.